Effects of induced mineral accretion on growth, survival and corallite properties of coral transplants - Sabater, Marlowe G. (2001)
The mineral accretion technique has an advntage of enhancing the survival of coral transplants, making their survival rate almost similar to that of undistributed colonies. This is of great importance in the field of coral reef rehabilation, particularly coral transplantation and coral farming, since the major setback of these techniques is that there are usually high mortalities due to transplantation stress. The corals are given a head start over their competitiors, usually fleshy algae, since the mineral accretion technique enables selective recruitment of only calcareous organisms. The recruitment of fleshy algae is suppressed due to the high alkalinity of the water surrounding the substrate brought about by the mineral accretion. There was a presence of a concentration gradient of mineral ions in the water column between the 2 electrodes where the highest concentration was found nearest to teh cathode substrate. growth enhancement was therefore localized at the small boundary above the cathode. Enhancement was brought about by the increase in mineral ion concentration which was used by the coral for the formation of their skeleton. An increase in ion concentration presumably increased the efficiency of uptake through passive diffusion and therefore decreased the active uptake effort. The energy saved from active upatke was re-channeled for reporduction through intratentacular budding. This resulted in an increase in the number of small coralities at the basal area of the nubbin. This is the first study to show phenotypic alteration brought about by increased concentration of mineral ions. The increase in the number of calcifying polyps at the basal area significantly enhanced the girth growth while longitudinal growth had only a slight increase. The ideal corals to be used for transplantation, therefore, are limited to the ones with encrusting growth forms if the objective is to enhance growth. Growth enhancement occured only in the presence of mineral accretion. Analysis of variance with required measures showed that significant difference in longitudinal growth occured only in the first four months after which differences in growth were no longer significant. Changes in coralite properties were no longer present after 12 months, indicating that alteration occured only in the presence of mineral accretion (which lasted for only the first 6 months of the long-term experiment). Overall, the effects of growth enhancement were localized both spatially (along the basal area) and temporally (only in the presence of mineral accretion). There was a prolonged effect, however, on survival. Applicantion of this technique for reef rehabilitation has to consider both the advantage one could get in using the technique and the cost of using such. Applying this technique at large spatial scales increases the cost bu the advantage that one could get in using the technique remains the same.
"December 2001."
Vita.
Research project funded by the University through the Office of the Vice-Chancellor for Research and Development (OVCRD).
Thesis (M.S. Marine Science)--University of the Philippines Diliman.
Keywords: Corals -- Effect of minerals on -- Philippines; Coral reef conservation -- Philippines -- Quezon Island (Pangasinan).; Corals -- Growth. -- Philippines